Optical film, method for producing optical film, optical member and image display device

By introducing silicon elements into the hard layer of the optical film and controlling the atomic proportion, the defects in the display characteristics caused by the reduction of the hard layer thickness in the optical film are solved, and higher display quality and equipment performance are achieved.

JP7663388B2Active Publication Date: 2025-04-16NITTO DENKO CORP
View PDF 8 Cites 0 Cited by

Patent Information

Application Number
JP2021051002
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Priority Date
2020-08-26
Filing Date
2021-03-25
Publication Date
2025-04-16
Estimated Expiration
2041-03-25

AI Technical Summary

Technical Problem

In attempts to make the image display device thinner, the reduction in the thickness of the hard layer in the optical film may lead to display characteristics defects such as ‘hajiki’, while additives are added to prevent the adhesion problems and contamination between the additional layer and the hard layer in this case may lead to display characteristics defects.

Method used

By introducing silicon elements into the hard layer of the optical film and controlling the atomic ratio at 0.1 nanometers deep on the layer surface, a silicon atom ratio is ensured to form a stable surface structure.

Benefits of technology

Effectively suppress or prevent defects in display characteristics, improve the performance of the optical film, and ensure the display quality of the image display device.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007663388000008
    Figure 0007663388000008
  • Figure 0007663388000009
    Figure 0007663388000009
  • Figure 0007663388000001
    Figure 0007663388000001
Patent Text Reader

Abstract

To provide an optical film for suppressing or preventing display characteristic failures.SOLUTION: An optical film 10 has a resin layer (B) 12 formed on a light permeable base material (A) 11, in which an element constituting the resin layer (B) 12 contains silicon, and in the resin layer (B) 12, an atomic number at a depth of 1 nm from the surface on a side opposite to the light permeable base material (A) 11 satisfies the following expression: 5.0≤[(nSi / ntotal)×100]≤9.0. In the expression, ntotal is the total of the atomic number of carbon, nitrogen, oxygen and silicon, and nSi is a silicon atomic number.SELECTED DRAWING: Figure 1
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to an optical film, a method for producing an optical film, an optical member, and an image display device. [Background technology]

[0002] Some optical films used in image display devices and the like have a resin layer, such as a hard coat layer, formed on a light-transmitting substrate (see Patent Document 1, etc.). In some cases, other layers are attached onto the resin layer. [Prior art documents] [Patent documents]

[0003] [Patent Document 1] JP 2008-221746 A Summary of the Invention [Problem to be solved by the invention]

[0004] In order to make devices such as image display devices thinner, it is preferable to make the optical films used therein as thin as possible.

[0005] However, in the optical film, when the thickness of the resin layer formed on the light-transmitting substrate is reduced, there is a risk of causing a display characteristic defect called cissing. On the other hand, when the amount of additive in the resin layer is increased in order to prevent cissing, there is a risk of causing a display characteristic defect due to contamination or peeling when another layer is attached onto the resin layer.

[0006] Therefore, an object of the present invention is to provide an optical film, a method for producing the optical film, an optical member, and an image display device in which defective display characteristics are suppressed or prevented. [Means for solving the problem]

[0007] In order to achieve the above object, the optical film of the present invention comprises: A resin layer (B) is formed on a light-transmitting substrate (A), The element constituting the resin layer (B) contains silicon, The resin layer (B) is characterized in that the number of atoms at a depth of 1 nm from the surface opposite to the light-transmitting substrate (A) satisfies the following mathematical formula (1). 5.0≦[(n Si / n total )×100]≦9.0 (1) In the formula (1), n total is the sum of the number of carbon, nitrogen, oxygen and silicon atoms, and n Si is the number of silicon atoms.

[0008] The method for producing the optical film of the present invention includes the steps of: The method includes a resin layer (B) forming step of forming the resin layer (B) on the light-transmitting substrate (A) so as to satisfy the mathematical formula (1), the resin layer (B) forming step includes a coating step of coating a resin layer forming coating liquid on the light-transmitting substrate (A), and a coating film forming step of drying the applied resin layer forming coating liquid to form a coating film, In the method for producing an optical film of the present invention, the resin layer-forming coating liquid contains a resin, a silicon-containing additive, and a dilution solvent.

[0009] The optical member of the present invention is an optical member that includes the optical film of the present invention.

[0010] The image display device of the present invention is an image display device that includes the optical film of the present invention or the optical member of the present invention. Effect of the Invention

[0011] According to the present invention, it is possible to provide an optical film, a method for producing an optical film, an optical member, and an image display device in which display characteristic defects are suppressed or prevented. [Brief description of the drawings]

[0012] [Figure 1] FIG. 1 is a cross-sectional view showing an example of the optical film of the present invention and the method for producing the same. [Diagram 2] FIG. 2 is a cross-sectional view showing another example of the optical film of the present invention. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0013] Next, the present invention will be described in more detail with reference to examples, but the present invention is not limited to the following description in any way.

[0014] In the optical film of the present invention, the resin layer (B) may have a thickness of 1.0 to 5.0 μm, for example.

[0015] In the optical film of the present invention, for example, the resin layer (B) may contain a surface conditioner, and the element constituting the surface conditioner may contain silicon.

[0016] In the optical film of the present invention, for example, the surface conditioner may contain a silicon compound having a dimethylsiloxane skeleton.

[0017] In the optical film of the present invention, for example, the resin layer (B) may be formed from a copolymer of an oligomer and a monomer having a functional group.

[0018] In the optical film of the present invention, for example, the resin layer (B) may be a hard coat layer.

[0019] In the optical film of the present invention, for example, another layer (C) may be attached via an adhesive layer to the surface of the resin layer (B) opposite to the light-transmitting substrate (A).

[0020] In the optical film of the present invention, for example, the pressure-sensitive adhesive layer may satisfy the condition of the following mathematical formula (2). Note that the method for measuring the water contact angles d1 and d2 in the following mathematical formula (2) is not particularly limited, and they can be measured, for example, by the method described in the examples below. (d1-d2) / d1≧0.10 (2) In the formula (2), d1 is the water contact angle (°) of the resin layer (B) surface when the adhesive layer and the other layer (C) are not present on the resin layer (B) surface, and d2 is the water contact angle (°) of the adhesive layer surface after the other layer (C) is peeled off from the adhesive layer. Note that the formula (2) is synonymous with d2 being 90% or less of d1 (reduced by 10% or more).

[0021] In the optical film of the present invention, for example, the other layer (C) may be a glass or resin film.

[0022] In the method for producing the optical film of the present invention, for example, the resin layer (B) forming step may further include a curing step of curing the coating film.

[0023] In the method for producing an optical film of the present invention, for example, the resin layer (B) in the optical film may contain a surface conditioner, the element constituting the surface conditioner may contain silicon, and the silicon element-containing additive may be the surface conditioner. The surface conditioner may contain, for example, a silicon compound having a dimethylsiloxane skeleton, as described above.

[0024] In the method for producing an optical film of the present invention, for example, the dilution solvent may contain MIBK (methyl isobutyl ketone) and cyclopentanone.

[0025] The optical member of the present invention may be, for example, a polarizing plate.

[0026] In the present invention, unless otherwise specified, "weight" and "mass" may be read interchangeably. For example, "parts by mass" may be read as "parts by weight", "parts by weight" may be read as "parts by mass", "% by mass" may be read as "% by weight", and "% by weight" may be read as "% by mass".

[0027] [1. Optical films] As described above, the optical film of the present invention has A resin layer (B) is formed on a light-transmitting substrate (A), The element constituting the resin layer (B) contains silicon, The resin layer (B) is characterized in that the number of atoms at a depth of 1 nm from the surface opposite to the light-transmitting substrate (A) satisfies the following mathematical formula (1). 5.0≦[(n Si / n total )×100]≦9.0 (1) In the formula (1), n total is the sum of the number of carbon, nitrogen, oxygen and silicon atoms, and n Si is the number of silicon atoms.

[0028] FIG. 1 shows an example of the optical film of the present invention and its manufacturing method. First, as shown in FIG. 1(a), a light-transmitting substrate (A) 11 is prepared. Next, as shown in FIG. 1(b), a resin layer (B) 12 is formed on one surface of the light-transmitting substrate (A) 11. The resin layer (B) 12 has an atomic number at a depth of 1 nm from the surface opposite to the light-transmitting substrate (A) 11 that satisfies the above-mentioned formula (1). In this manner, the optical film 10 of the present invention shown in FIG. 1(b) can be manufactured. The manufacturing method of the optical film of the present invention will be described in detail later.

[0029] Furthermore, as shown in FIG. 1(c), another layer (C) 20 may be attached to the surface of the resin layer (B) 12 opposite the light-transmitting substrate (A) 11 via an adhesive layer 13 to form an optical film 10' of the present invention including the another layer (C) 20.

[0030] Another example of the optical film of the present invention is shown in the cross-sectional view of Fig. 2. As shown in the figure, this optical film 10 has a resin layer (B) 12 laminated on one surface of a light-transmitting substrate (A) 11. In the optical film 10 of Fig. 2, the resin layer (B) 12 is an antiglare hard coat layer. The antiglare hard coat layer (B) 12 contains particles 12b and a thixotropy-imparting agent 12c in a resin layer-forming resin 12a.

[0031] In the present invention, the resin layer (B) may be formed only of a resin, but may also contain other components. The other components are not particularly limited and may be one or more kinds, and may be, for example, particles, a thixotropy-imparting agent, etc., as shown in FIG. 2.

[0032] In addition, the surface of the resin layer (B) opposite to the light-transmitting substrate (A) may be flat, or may have irregularities, for example, as shown in Fig. 2. In the present invention, the "depth" from the surface of the resin layer (B) opposite to the light-transmitting substrate (A) refers to the depth in the direction perpendicular to the surface of the light-transmitting substrate (A), and this applies whether the surface is flat or has irregularities.

[0033] As described above, in the optical film of the present invention, the number of atoms in the resin layer (B) at a depth of 1 nm from the surface opposite to the light-transmitting substrate (A) satisfies the formula (1). Satisfying the formula (1) is synonymous with the number of silicon atoms being 5.0 to 9.0% relative to the total number of carbon, nitrogen, oxygen and silicon atoms in the resin layer (B) at a depth of 1 nm from the surface opposite to the light-transmitting substrate (A). The number of silicon atoms may be, for example, 5.5% or more, 6.0% or more, or 6.5% or more, or may be, for example, 8.5% or less, 8.0% or less, or 7.5% or less, relative to the total number of carbon, nitrogen, oxygen and silicon atoms at a depth of 1 nm from the surface opposite to the light-transmitting substrate (A).

[0034] As defined by the formula (1), the resin layer (B) necessarily contains silicon as an element. The resin layer (B) may contain all (three) of the elements carbon, nitrogen, and oxygen, but may not contain all of them, and may contain only one or two of them. The resin layer (B) may or may not contain elements other than carbon, nitrogen, oxygen, and silicon.

[0035] The thickness of the resin layer (B) may be, for example, 1.0 to 5.0 μm as described above. The thickness of the resin layer (B) may be, for example, 1.5 μm or more, or, for example, 4.5 μm or less, 4.0 μm or less, 3.5 μm or less, 3.0 μm or less, or 2.5 μm or less.

[0036] Hereinafter, the light-transmitting substrate (A), the resin layer (B), the pressure-sensitive adhesive layer, and the other layer (C) will be further described with examples.

[0037] The light-transmitting substrate (A) is not particularly limited, and examples thereof include transparent plastic film substrates. The transparent plastic film substrate is not particularly limited, and is preferably one having excellent visible light transmittance (preferably 90% or more light transmittance) and excellent transparency (preferably 1% or less haze value), and examples thereof include the transparent plastic film substrates described in JP-A-2008-90263. As the transparent plastic film substrate, one having optically low birefringence is preferably used. The optical film of the present invention can be used, for example, as a protective film for a polarizing plate, and in this case, the transparent plastic film substrate is preferably a film formed from triacetyl cellulose (TAC), polycarbonate, an acrylic polymer, a polyolefin having a cyclic or norbornene structure, or the like. In addition, in the present invention, as described later, the transparent plastic film substrate may be a polarizer itself. With such a configuration, a protective layer made of TAC or the like is not required, and the structure of the polarizing plate can be simplified, so that the number of manufacturing steps for the polarizing plate or image display device can be reduced, and production efficiency can be improved. In addition, such a configuration allows the polarizing plate to be made thinner. When the transparent plastic film substrate is a polarizer, the resin layer (B) and the other layer (C) serve as protective layers. In addition, such a configuration allows the optical film to also function as a cover plate when attached to the surface of a liquid crystal cell, for example.

[0038] In the present invention, the thickness of the light-transmitting substrate (A) is not particularly limited, but considering the strength, workability such as handleability, and thin layer property, it is, for example, in the range of 10 to 500 μm, 20 to 300 μm, or 30 to 200 μm. The refractive index of the light-transmitting substrate (A) is not particularly limited. The refractive index is, for example, in the range of 1.30 to 1.80 or 1.40 to 1.70.

[0039] In the optical film of the present invention, for example, the resin contained in the light-transmitting substrate (A) may contain an acrylic resin.

[0040] In the optical film of the present invention, for example, the light-transmitting substrate (A) may be an acrylic film.

[0041] In the optical film of the present invention, for example, the surface of the resin layer (B) opposite to the light-transmitting substrate may have irregularities, and the external haze value due to the irregularities may be 5% or more. In a highly antiglare film, the overall appearance may be blurred and a black and white shading pattern may easily occur. From the viewpoint of suppressing or preventing this and suppressing reflection, it is preferable that the external haze value is as large as possible. On the other hand, from the viewpoint of suppressing or preventing deterioration of display characteristics (for example, image becomes unclear, contrast in a dark place decreases, etc.), it is preferable that the external haze value is not too large. The external haze value is not particularly limited, but may be, for example, 5% or more, 10% or more, 15% or more, or 20% or more, and may be, for example, 50% or less, 45% or less, 40% or less, or 35% or less. In the present invention, the method for measuring the external haze value is not particularly limited, but may be, for example, the following measurement methods (1) to (3). (1) The total haze value of the optical film of the present invention is measured based on the method in accordance with JIS K 7136. (2) A light-transmitting adhesive is laminated on the surface of the resin layer (B) of the optical film (1) opposite to the light-transmitting substrate (A), and a COP film (ZEONOR film, manufactured by Zeon Corporation) is attached thereon to produce a laminate. This laminate is measured using the same method as the total haze measurement method in accordance with JIS K 7136 (i.e., the measurement method in (1) above), to obtain the internal haze value of the optical film (1). This internal haze value is the haze value obtained by excluding the influence of the unevenness of the outermost surface on the resin layer (B) side from the total haze value in (1) above. (3) The value obtained by subtracting the internal haze value measured in (2) above from the total haze value measured in (1) above is defined as the external haze value of the optical film in (1) above.

[0042] In the optical film of the present invention, the resin contained in the resin layer (B) is not particularly limited, but may contain, for example, an acrylate resin (also called an acrylic resin).

[0043] In the optical film of the present invention, for example, the resin contained in the resin layer (B) may contain a urethane acrylate resin.

[0044] In the optical film of the present invention, for example, as described above, the resin layer (B) may be formed of a copolymer of an oligomer having a functional group and a monomer. The oligomer having a functional group is not particularly limited, but examples thereof include curable urethane acrylate resins. Examples of the curable urethane acrylate resins include a product name "UV-1700TL" manufactured by Mitsubishi Chemical Corporation. Examples of the monomers include, but are not particularly limited, polyfunctional acrylates. Examples of the polyfunctional acrylates include a product name "M-920" manufactured by Toa Gosei Co., Ltd.

[0045] In the optical film of the present invention, for example, the resin contained in the resin layer (B) may be a copolymer of a curable urethane acrylate resin and a polyfunctional acrylate.

[0046] In the optical film of the present invention, the resin layer (B) necessarily contains silicon as an element, as described above. Therefore, as described above, the resin layer (B) may contain a surface conditioner, and the element constituting the surface conditioner may contain silicon. The surface conditioner may also contain a silicon compound having a dimethylsiloxane skeleton. The surface conditioner may be, for example, a leveling agent, a dimethylsiloxane-modified methacrylic acid ester, a polydimethylsiloxane cyclic compound, or the like. Examples of the surface conditioner include "LE-303" manufactured by Kyoeisha Chemical Co., Ltd. and "PC4100" manufactured by DIC Corporation. The amount of the surface conditioner to be added is not particularly limited, but may be appropriately set so that the silicon content in the resin layer (B) is within the above-mentioned range, for example.

[0047] In the optical film of the present invention, the resin layer (B) is not particularly limited, and may be, for example, a hard coat layer, for example, an antiglare hard coat layer.

[0048] In the optical film of the present invention, for example, the resin layer (B) may be formed using an antiglare hard coat layer forming material containing a resin and a filler, and the resin layer (B) may have an aggregation portion in which the filler aggregates to form a convex portion on the surface of the resin layer (B). In addition, in the aggregation portion forming the convex portion, the filler may be present in a state in which a plurality of fillers are gathered in one direction in the surface direction of the resin layer (B). In the image display device of the present invention, for example, the optical film of the present invention may be arranged so that the one direction in which a plurality of fillers are gathered coincides with the long side direction of the black matrix pattern. Examples of the filler include the particles and the thixotropy-imparting agent.

[0049] The resin layer (B) is formed, for example, by applying a coating liquid containing a resin, a silicon-containing additive, and a dilution solvent onto the surface of the light-transmitting substrate (A) to form a coating film, and then removing the solvent from the coating film, as described below. Examples of the resin include a thermosetting resin and an ionizing radiation curable resin that is cured by ultraviolet light or light. As the resin, commercially available thermosetting resins, ultraviolet curable resins, etc. can also be used.

[0050] As the thermosetting resin or ultraviolet curing resin, for example, a curable compound having at least one of an acrylate group and a methacrylate group that is cured by heat, light (ultraviolet light, etc.), electron beam, etc. can be used, and examples thereof include oligomers or prepolymers of acrylates and methacrylates of polyfunctional compounds such as silicone resins, polyester resins, polyether resins, epoxy resins, urethane resins, alkyd resins, spiroacetal resins, polybutadiene resins, polythiolpolyene resins, polyhydric alcohols, etc. These may be used alone or in combination of two or more types.

[0051] The resin may be, for example, a reactive diluent having at least one of an acrylate group and a methacrylate group. The reactive diluent may be, for example, a reactive diluent described in JP-A-2008-88309, and may include, for example, a monofunctional acrylate, a monofunctional methacrylate, a polyfunctional acrylate, and a polyfunctional methacrylate. The reactive diluent is preferably a trifunctional or higher acrylate or a trifunctional or higher methacrylate. This is because the hardness of the resin layer (B) can be excellent. The reactive diluent may be, for example, butanediol glycerin ether diacrylate, an acrylate of isocyanuric acid, a methacrylate of isocyanuric acid, and the like. These may be used alone or in combination of two or more.

[0052] As described above, the resin layer (B) may or may not contain a thixotropy-imparting agent. The thixotropy-imparting agent may be, for example, at least one selected from the group consisting of organic clay, oxidized polyolefin, and modified urea. The thixotropy-imparting agent may be, for example, a thickener. The thixotropy-imparting agent may be used alone or in combination of two or more kinds.

[0053] In the optical film of the present invention, the resin layer (B) may contain, for example, 0.2 to 5 mass % or 0.4 to 4 mass % of the thixotropy-imparting agent relative to the total mass of the resin forming the resin layer.

[0054] The other layer (C) is not particularly limited and may be, for example, a protective layer, a decorative layer, etc. The other layer (C) may be, for example, a glass or resin film (plastic film). The resin film is not particularly limited, but may be, for example, the "E-MASK" series manufactured by Nitto Denko Corporation. The thickness of the other layer (C) is not particularly limited and may be, for example, 10 μm or more, 20 μm or more, or 30 μm or more, or may be, for example, 80 μm or less, 70 μm or less, 60 μm or less, 50 μm or less, or 40 μm or less.

[0055] The adhesive layer may be, for example, an adhesive layer formed of an adhesive (adhesive composition). In the present invention, the adhesive layer is preferably a layer that allows the other layer (C) to be peeled off from the resin layer (B). The thickness of the adhesive layer is not particularly limited, but may be, for example, 5 μm or more, or 10 μm or more, and may be, for example, 50 μm or less, 40 μm or less, 30 μm or less, or 20 μm or less. The adhesive is not particularly limited, but examples thereof include (meth)acrylic polymers. These may be dissolved or dispersed in a solvent to form a solution or dispersion, which may be used as the adhesive (adhesive composition). Examples of the solvent include ethyl acetate, and only one type may be used, or multiple types may be used in combination. The concentration of the solute or dispersoid (for example, the acrylic polymer) in the solution or dispersion may be, for example, 10 mass% or more, or 15 mass% or more, and may be, for example, 60 mass% or less, 50 mass% or less, 40 mass% or less, or 25 mass% or less. In the present invention, the term "(meth)acrylic polymer" refers to a polymer or copolymer of at least one monomer selected from the group consisting of (meth)acrylic acid, (meth)acrylic acid esters, and (meth)acrylamide. In the present invention, the term "(meth)acrylic acid" refers to "at least one of acrylic acid and methacrylic acid," and the term "(meth)acrylic acid ester" refers to "at least one of acrylic acid esters and methacrylic acid esters." Examples of the (meth)acrylic acid esters include linear or branched alkyl esters of (meth)acrylic acid. In the linear or branched alkyl esters of (meth)acrylic acid, the number of carbon atoms of the alkyl group may be, for example, 1 or more, 2 or more, 3 or more, or 4 or more, and may be, for example, 18 or less, 16 or less, 14 or less, 12 or less, 10 or less, or 8 or less. The alkyl group may be, for example, substituted with one or more substituents or may not be substituted. Examples of the substituents include hydroxyl groups, and when there are multiple substituents, they may be the same or different. Specific examples of the (meth)acrylic acid ester include 2-ethylhexyl acrylate, 2-hydroxyethyl acrylate, and 4-hydroxybutyl acrylate.The pressure-sensitive adhesive may be used alone or in combination of two or more kinds.

[0056] The optical film of the present invention may or may not include a layer other than the light-transmitting substrate (A), the resin layer (B), the adhesive layer, and the other layer (C). The other layer is not particularly limited, and examples thereof include an easy-adhesion layer, an antireflection layer, and a substrate layer to which an adhesive is attached.

[0057] As described above, in an optical film, if the thickness of a resin layer formed on a light-transmitting substrate is reduced, a display characteristic defect called cissing may occur. On the other hand, if the amount of additives (e.g., surface conditioners such as leveling agents) in the resin layer is increased in order to prevent cissing, when another layer is attached onto the resin layer, the display characteristic defect may also occur due to contamination or peeling. In contrast, in the present invention, by making the resin layer (B) satisfy the formula (1), for example, it is possible to suppress or prevent the contamination, peeling, etc., and as a result, it is possible to provide an optical film in which display characteristic defects are suppressed or prevented.

[0058] [2. Manufacturing method of optical film] The method for producing the optical film of the present invention is not particularly limited, and the film may be produced by any method, but it is preferable to produce the optical film by the above-mentioned method for producing the optical film of the present invention.

[0059] The optical film can be produced, for example, as follows.

[0060] First, the resin layer (B) is formed on the light-transmitting substrate (A) so as to satisfy the formula (1) (resin layer (B) forming step). This produces a laminate of the light-transmitting substrate (A) and the resin layer (B). As described above, the resin layer (B) forming step includes a coating step of coating the resin layer forming coating liquid (hereinafter, sometimes simply referred to as "coating liquid" or "resin layer (B) forming material") on the light-transmitting substrate (A), and a coating film forming step of drying the applied coating liquid to form a coating film. Also, for example, as described above, the resin layer (B) forming step may further include a curing step of curing the coating film. The curing may be performed, for example, after the drying, but is not limited thereto. The curing may be performed, for example, by heating, light irradiation, or the like. The light is not particularly limited, but may be, for example, ultraviolet light, or the like. The light source for the light irradiation is also not particularly limited, but may be, for example, a high-pressure mercury lamp, or the like.

[0061] As described above, the coating liquid (resin layer (B) forming material) contains the resin, the silicon-containing additive, and the dilution solvent (hereinafter, sometimes simply referred to as "solvent"). The coating liquid may or may not contain other components other than these. The other components are not particularly limited, but examples thereof include the particles, the thixotropy-imparting agent, etc.

[0062] The solvent is not particularly limited, and various solvents can be used, and one type may be used alone, or two or more types may be used in combination. In order to obtain the optical film of the present invention, the optimal type of solvent and solvent ratio may be appropriately selected according to the composition of the resin, the type and content of the particles and the thixotropy-imparting agent, etc. The solvent is not particularly limited, and examples thereof include alcohols such as methanol, ethanol, isopropyl alcohol (IPA), butanol, t-butyl alcohol (TBA), and 2-methoxyethanol; ketones such as acetone, methyl ethyl ketone, methyl isobutyl ketone, and cyclopentanone; esters such as methyl acetate, ethyl acetate, and butyl acetate; ethers such as diisopropyl ether and propylene glycol monomethyl ether; glycols such as ethylene glycol and propylene glycol; cellosolves such as ethyl cellosolve and butyl cellosolve; aliphatic hydrocarbons such as hexane, heptane, and octane; and aromatic hydrocarbons such as benzene, toluene, and xylene. In addition, for example, the solvent may include a hydrocarbon solvent and a ketone solvent. The hydrocarbon solvent may be, for example, an aromatic hydrocarbon. The aromatic hydrocarbon may be, for example, at least one selected from the group consisting of toluene, o-xylene, m-xylene, p-xylene, ethylbenzene, and benzene. The ketone solvent may be, for example, at least one selected from the group consisting of cyclopentanone, acetone, methyl ethyl ketone, methyl isobutyl ketone, diethyl ketone, cyclohexanone, isophorone, and acetophenone. The solvent preferably contains the hydrocarbon solvent (for example, toluene) in order to dissolve a thixotropy-imparting agent (for example, a thickener). The solvent may be, for example, a solvent in which the hydrocarbon solvent and the ketone solvent are mixed in a mass ratio of 90:10 to 10:90. The mass ratio of the hydrocarbon solvent and the ketone solvent may be, for example, 80:20 to 20:80, 70:30 to 30:70, or 40:60 to 60:40, etc. In this case, for example, the hydrocarbon solvent may be toluene and the ketone solvent may be methyl ethyl ketone.The solvent may include, for example, toluene and may further include at least one selected from the group consisting of ethyl acetate, butyl acetate, IPA, methyl isobutyl ketone, methyl ethyl ketone, methanol, ethanol, and TBA.

[0063] When an acrylic film is used as the light-transmitting substrate (A) to form an intermediate layer (permeation layer), a good solvent for the acrylic film (acrylic resin) can be suitably used. The solvent may be, for example, a solvent containing a hydrocarbon solvent and a ketone solvent, as described above. The hydrocarbon solvent may be, for example, an aromatic hydrocarbon. The aromatic hydrocarbon may be, for example, at least one selected from the group consisting of toluene, o-xylene, m-xylene, p-xylene, ethylbenzene, and benzene. The ketone solvent may be, for example, at least one selected from the group consisting of cyclopentanone, acetone, methyl ethyl ketone, methyl isobutyl ketone, diethyl ketone, cyclohexanone, isophorone, and acetophenone. The solvent may be, for example, a solvent obtained by mixing the hydrocarbon solvent and the ketone solvent in a mass ratio of 90:10 to 10:90. The mass ratio of the hydrocarbon solvent to the ketone solvent may be, for example, 80:20 to 20:80, 70:30 to 30:70, or 40:60 to 60:40, etc. In this case, for example, the hydrocarbon solvent may be toluene, and the ketone solvent may be methyl ethyl ketone.

[0064] When triacetyl cellulose (TAC) is used as the light-transmitting substrate (A), the solvent is not particularly limited, and examples thereof include ethyl acetate, methyl ethyl ketone, MIBK (methyl isobutyl ketone), cyclopentanone, etc., and may be used alone or in combination. In this case, the solvent may be, for example, a mixed solvent of MIBK and cyclopentanone. The mixing ratio of MIBK and cyclopentanone is not particularly limited, and may be, for example, 90:10 to 10:90, 80:20 to 20:80, or 70:30 to 30:70 by mass ratio.

[0065] In addition, by appropriately selecting solvent, when containing thixotropy-imparting agent, it is possible to well express the thixotropy in antiglare hard coat layer forming material (coating liquid).For example, when using organic clay, toluene and xylene can be preferably used alone or in combination; for example, when using oxidized polyolefin, methyl ethyl ketone, ethyl acetate, propylene glycol monomethyl ester can be preferably used alone or in combination; for example, when using modified urea, butyl acetate and methyl isobutyl ketone can be preferably used alone or in combination.

[0066] Various leveling agents can be added to the resin layer (B) forming material. As the leveling agent, for example, a fluorine-based or silicone-based leveling agent can be used for the purpose of preventing uneven coating (uniformity of the coating surface). Silicone-based leveling agents can also be used for the purpose of incorporating elemental silicon into the resin layer (B). In the present invention, a leveling agent can be appropriately selected depending on the case where antifouling properties are required on the surface of the resin layer (B) or the case where an antireflection layer (low refractive index layer) or a layer containing an interlayer filler is formed on the resin layer (B) as the other layer (C).

[0067] The amount of the leveling agent added is, for example, 5 parts by weight or less, and preferably in the range of 0.01 to 5 parts by weight, relative to 100 parts by weight of the resin.

[0068] The resin layer (B) forming material may contain, if necessary, pigments, fillers, dispersants, plasticizers, ultraviolet absorbers, surfactants, antifouling agents, antioxidants, etc., within the scope of not impairing the performance. These additives may be used alone or in combination of two or more.

[0069] As the material for forming the resin layer (B), for example, a conventionally known photopolymerization initiator such as that described in JP-A-2008-88309 can be used.

[0070] Examples of a method for forming a coating film by applying the resin layer (B) forming material (coating liquid) onto the light-transmitting substrate (A) include coating methods such as fountain coating, die coating, spray coating, gravure coating, roll coating, and bar coating.

[0071] Next, as described above, the coating film is dried and cured to form the resin layer (B). The drying may be, for example, natural drying, air drying by blowing air, heat drying, or a combination of these methods.

[0072] The drying temperature of the resin layer (B) forming material (coating liquid) may be, for example, in the range of 30 to 200° C. The drying temperature may be, for example, 40° C. or more, 50° C. or more, 60° C. or more, 70° C. or more, 80° C. or more, 90° C. or more, or 100° C. or more, and may be 190° C. or less, 180° C. or less, 170° C. or less, 160° C. or less, 150° C. or less, 140° C. or less, 135° C. or less, 130° C. or less, 120° C. or less, or 110° C. or less. The drying time is not particularly limited, and may be, for example, 30 seconds or more, 40 seconds or more, 50 seconds or more, or 60 seconds or more, and may be 150 seconds or less, 130 seconds or less, 110 seconds or less, or 90 seconds or less.

[0073] The method for curing the coating film is not particularly limited, but ultraviolet curing is preferred. The radiation dose of the energy ray source is 50 to 500 mJ / cm2 as the cumulative exposure dose at an ultraviolet wavelength of 365 nm. 2 The irradiation dose is preferably 50 mJ / cm. 2 If the curing rate is 500 mJ / cm or more, the curing is likely to proceed sufficiently, and the hardness of the resin layer (B) formed is likely to be high. 2 If it is equal to or less than this, coloring of the resin layer (B) to be formed can be prevented.

[0074] In the manner described above, a laminate of the light-transmitting substrate (A) and the resin layer (B) can be produced. This laminate may be used as the optical film of the present invention as it is, or, for example, the optical film of the present invention may be obtained by attaching the other layer (C) to the surface of the resin layer (B) opposite to the light-transmitting substrate (A) via the adhesive layer.

[0075] [3. Optical components and image display devices] The optical member of the present invention is not particularly limited, but may be, for example, a polarizing plate. The polarizing plate is also not particularly limited, but may include, for example, the optical film of the present invention and a polarizer, and may further include other components. Each component of the polarizing plate may be bonded together, for example, with an adhesive or a pressure sensitive adhesive.

[0076] The image display device of the present invention is not particularly limited, and any image display device may be used, and examples thereof include a liquid crystal display device and an organic EL display device.

[0077] The image display device of the present invention is, for example, an image display device having the optical film of the present invention on the viewing side surface, and the image display device may have a black matrix pattern.

[0078] The optical film of the present invention can be laminated, for example, on the light-transmitting substrate (A) side to an optical member used in an LCD via a pressure-sensitive adhesive or adhesive. In addition, in this lamination, the surface of the light-transmitting substrate (A) may be subjected to various surface treatments as described above. As described above, according to the manufacturing method of the optical film of the present invention, the surface shape of the optical film can be freely controlled in a wide range. Therefore, the optical properties that can be obtained by laminating the optical film with another optical member using an adhesive or pressure-sensitive adhesive cover a wide range corresponding to the surface shape of the optical film.

[0079] The optical member may be, for example, a polarizer or a polarizing plate. A polarizing plate is generally configured to have a transparent protective film on one or both sides of a polarizer. When transparent protective films are provided on both sides of a polarizer, the transparent protective films on the front and back may be made of the same material or different materials. The polarizing plates are usually disposed on both sides of a liquid crystal cell. Moreover, the polarizing plates are disposed so that the absorption axes of the two polarizing plates are approximately perpendicular to each other.

[0080] The configuration of the polarizing plate having the optical film laminated thereon is not particularly limited, and may be, for example, a configuration in which a transparent protective film, the polarizer, and the transparent protective film are laminated in this order on the optical film, or a configuration in which the polarizer and the transparent protective film are laminated in this order on the optical film.

[0081] The image display device of the present invention has the same structure as a conventional image display device, except that the optical film is arranged in a specific direction. For example, in the case of an LCD, it can be manufactured by appropriately assembling each component such as a liquid crystal cell, optical members such as a polarizing plate, and an illumination system (backlight, etc.) as necessary, and incorporating a driving circuit.

[0082] The optical film of the present invention can be used for any purpose without any particular limitation, for example, office automation equipment such as personal computer monitors, notebook computers, and copy machines, portable devices such as mobile phones, watches, digital cameras, personal digital assistants (PDAs), and portable game consoles, home electric appliances such as video cameras, televisions, and microwave ovens, in-vehicle devices such as back monitors, monitors for car navigation systems, and car audio, exhibition devices such as information monitors for commercial stores, security devices such as surveillance monitors, and nursing and medical devices such as nursing monitors and medical monitors. EXAMPLES

[0083] Next, examples of the present invention will be described together with comparative examples, although the present invention is not limited to the following examples and comparative examples.

[0084] In the following examples and comparative examples, the number of parts of a substance is by mass (parts by weight) unless otherwise specified.

[0085] [Example 1] An optical film of the present invention having a resin layer (hard coat layer) (B) formed on a light-transmitting substrate (A) was produced as follows.

[0086] As the resin contained in the hard coat layer, 40 parts by weight of ultraviolet-curable acrylate resin (manufactured by Toa Gosei Co., Ltd., product name "M-920", solid content 100%) and 60 parts by weight of ultraviolet-curable acrylate resin (manufactured by Mitsubishi Chemical Corporation, product name "UV-1700TL", solid content 80%) were prepared. Per 100 parts by weight of the resin solid content of the resin, 3 parts by weight of photopolymerization initiator (manufactured by BASF, product name "OMNIRAD907") and 0.12 parts by weight of leveling agent (manufactured by Kyoeisha Chemical Co., Ltd., product name "LE-303", solid content 40%) were mixed. This mixture was diluted with a MIBK / cyclopentanone mixed solvent (weight ratio 70 / 30) so that the solid content concentration was 30%, to prepare a coating liquid (E1) for forming a hard coat layer.

[0087] A transparent plastic film substrate (TAC, manufactured by Konica Minolta, Inc., product name "KC2UA") was prepared as the light-transmitting substrate (A). Next, the hard coat layer-forming coating liquid (E1) was applied (coated) to one side of the transparent plastic film substrate using a bar coater to form a coating layer (coating layer) (coating process). The transparent plastic film substrate on which the coating layer was formed was transported to a drying process (coating film forming process). Furthermore, in the drying process (coating film forming process), the coating layer was dried by heating at 80°C for 1 minute to form a coating film. Thereafter, the coating film was irradiated with a high-pressure mercury lamp with an integrated light amount of 240 mJ / cm. 2 The coating film was cured (curing step) by irradiation with ultraviolet light of 1000 nm to form a hard coat layer (resin layer (B)) having a thickness of 2.0 μm. In this manner, a hard coat film (optical film) of Example 1 in which the resin layer (B) was formed on the light-transmitting substrate (A) was obtained.

[0088] [Example 2] An optical film of the present invention having a resin layer (hard coat layer) (B) formed on a light-transmitting substrate (A) was produced as follows.

[0089] As the resin contained in the hard coat layer, 40 parts by weight of ultraviolet-curable acrylate resin (manufactured by Toa Gosei Co., Ltd., product name "M-920", solid content 100%) and 60 parts by weight of ultraviolet-curable acrylate resin (manufactured by Mitsubishi Chemical Corporation, product name "UV-1700TL", solid content 80%) were prepared. Per 100 parts by weight of the resin solid content of the resin, 3 parts by weight of photopolymerization initiator (manufactured by BASF, product name "OMNIRAD907") and 0.20 parts by weight of leveling agent (manufactured by Kyoeisha Chemical Co., Ltd., product name "LE-303", solid content 40%) were mixed. This mixture was diluted with a MIBK / cyclopentanone mixed solvent (weight ratio 70 / 30) so that the solid content concentration was 30%, to prepare a coating liquid (E2) for forming a hard coat layer.

[0090] A transparent plastic film substrate (TAC, manufactured by Konica Minolta, Inc., product name "KC2UA") was prepared as the light-transmitting substrate (A). Next, the hard coat layer-forming coating liquid (E2) was applied (coated) to one surface of the transparent plastic film substrate using a bar coater to form a coating layer (coating layer) (coating process). The transparent plastic film substrate on which the coating layer was formed was transported to a drying process (coating film forming process). Furthermore, in the drying process (coating film forming process), the coating layer was dried by heating at 80°C for 1 minute to form a coating film. Thereafter, the coating film was irradiated with a high-pressure mercury lamp with an integrated light amount of 240 mJ / cm. 2 The coating film was cured (curing step) by irradiation with ultraviolet light of 1000 nm to form a hard coat layer (resin layer (B)) having a thickness of 2.0 μm. In this manner, a hard coat film (optical film) of Example 2 in which the resin layer (B) was formed on the light-transmitting substrate (A) was obtained.

[0091] [Example 3] An optical film of the present invention having a resin layer (hard coat layer) (B) formed on a light-transmitting substrate (A) was produced as follows.

[0092] As the resin contained in the hard coat layer, 50 parts by weight of ultraviolet-curable acrylate resin (manufactured by Shin-Nakamura Chemical Co., Ltd., trade name "A-DCP", solid content 100%) and 50 parts by weight of ultraviolet-curable acrylate resin (manufactured by Mitsubishi Chemical Co., Ltd., trade name "UV-1700TL", solid content 80%) were prepared. 5 parts by weight of photopolymerization initiator (manufactured by BASF, trade name "OMNIRAD907") and 0.20 parts by weight of leveling agent (manufactured by Kyoeisha Chemical Co., Ltd., trade name "LE-303", solid content 40%) were mixed per 100 parts by weight of the resin solid content. This mixture was diluted with a MIBK / cyclopentanone mixed solvent (weight ratio 60 / 40) so that the solid content concentration was 30%, to prepare a coating liquid (E3) for forming a hard coat layer.

[0093] A transparent plastic film substrate (TAC, manufactured by Fujifilm Corporation, product name "TJ25UL") was prepared as the light-transmitting substrate (A). Next, the hard coat layer forming coating liquid (E3) was applied (coated) to one side of the transparent plastic film substrate using a bar coater to form a coating layer (coating layer) (coating process). The transparent plastic film substrate on which this coating layer was formed was transported to a drying process (coating film forming process). Furthermore, in the drying process (coating film forming process), the coating layer was dried by heating at 60°C for 1 minute to form a coating film. Thereafter, the coating film was irradiated with a high-pressure mercury lamp with an integrated light amount of 220 mJ / cm. 2 The coating film was cured (curing step) by irradiation with ultraviolet light of 1000 nm to form a hard coat layer (resin layer (B)) having a thickness of 2.5 μm. In this manner, a hard coat film (optical film) of Example 3 in which the resin layer (B) was formed on the light-transmitting substrate (A) was obtained.

[0094] [Example 4] An optical film of the present invention having a resin layer (hard coat layer) (B) formed on a light-transmitting substrate (A) was produced as follows.

[0095] As the resin contained in the hard coat layer, 50 parts by weight of ultraviolet-curable acrylate resin (manufactured by Shin-Nakamura Chemical Co., Ltd., trade name "A-DCP", solid content 100%) and 50 parts by weight of ultraviolet-curable acrylate resin (manufactured by Mitsubishi Chemical Co., Ltd., trade name "UV-1700TL", solid content 80%) were prepared. 5 parts by weight of photopolymerization initiator (manufactured by BASF, trade name "OMNIRAD907") and 0.10 parts by weight of leveling agent (manufactured by Kyoeisha Chemical Co., Ltd., trade name "LE-303", solid content 40%) were mixed per 100 parts by weight of the resin solid content. This mixture was diluted with a MIBK / cyclopentanone mixed solvent (weight ratio 60 / 40) so that the solid content concentration was 30%, to prepare a coating liquid (E4) for forming a hard coat layer.

[0096] A transparent plastic film substrate (TAC, manufactured by Fujifilm Corporation, product name "TJ25UL") was prepared as the light-transmitting substrate (A). The hard coat layer-forming coating liquid (E4) was applied (coated) to one side of the transparent plastic film substrate using a bar coater to form a coating layer (coating layer) (coating process). The transparent plastic film substrate on which the coating layer was formed was transported to a drying process (coating film forming process). Furthermore, in the drying process (coating film forming process), the coating layer was dried by heating at 60°C for 1 minute to form a coating film. Thereafter, the coating film was irradiated with a high-pressure mercury lamp with an integrated light amount of 220 mJ / cm. 2 The coating film was cured (curing step) by irradiation with ultraviolet light of 1000 nm to form a hard coat layer (resin layer (B)) having a thickness of 2.5 μm. In this manner, a hard coat film (optical film) of Example 4 in which the resin layer (B) was formed on the light-transmitting substrate (A) was obtained.

[0097] [Comparative Example 1] An optical film having a resin layer (hard coat layer) formed on a light-transmitting substrate was produced in the following manner.

[0098] As the resin contained in the hard coat layer, 40 parts by weight of ultraviolet-curable acrylate resin (manufactured by Toa Gosei Co., Ltd., product name "M-920", solid content 100%) and 60 parts by weight of ultraviolet-curable acrylate resin (manufactured by Mitsubishi Chemical Corporation, product name "UV-1700TL", solid content 80%) were prepared. Per 100 parts by weight of the resin solid content of the resin, 3 parts by weight of photopolymerization initiator (manufactured by BASF, product name "OMNIRAD907") and 0.01 parts by weight of leveling agent (manufactured by DIC Corporation, product name "PC4100", solid content 40%) were mixed. This mixture was diluted with a MIBK / cyclopentanone mixed solvent (weight ratio 72 / 28) so that the solid content concentration was 25%, to prepare a coating liquid (C1) for forming a hard coat layer.

[0099] A transparent plastic film substrate (TAC, manufactured by Konica Minolta, Inc., product name "KC2UA") was prepared as a light-transmitting substrate. This light-transmitting substrate (transparent plastic film substrate) was the same as the light-transmitting substrate (A) of Example 1. The hard coat layer-forming coating liquid (C1) was applied (coated) to one surface of the transparent plastic film substrate using a bar coater to form a coating layer (coating layer). Then, the transparent plastic film substrate on which this coating layer was formed was transported to a drying process. In the drying process, the coating layer was dried by heating at 80°C for 1 minute to form a coating film. Thereafter, the coating film was irradiated with a high-pressure mercury lamp with an integrated light amount of 240 mJ / cm. 2 The coating film was cured by irradiating it with ultraviolet light of 1.0 .mu.m to form a hard coat layer having a thickness of 2.0 .mu.m. In this manner, a hard coat film of Comparative Example 1 in which the hard coat layer was formed on the light-transmitting substrate was obtained.

[0100] [Comparative Example 2] An optical film having a resin layer (hard coat layer) formed on a light-transmitting substrate was produced in the following manner.

[0101] As the resin contained in the hard coat layer, 40 parts by weight of ultraviolet-curable acrylate resin (manufactured by Toa Gosei Co., Ltd., product name "M-920", solid content 100%) and 60 parts by weight of ultraviolet-curable acrylate resin (manufactured by Mitsubishi Chemical Corporation, product name "UV-1700TL", solid content 80%) were prepared. Per 100 parts by weight of the resin solid content of the resin, 3 parts by weight of photopolymerization initiator (manufactured by BASF, product name "OMNIRAD907") and 0.10 parts by weight of leveling agent (manufactured by Kyoeisha Chemical Co., Ltd., product name "LE-303", solid content 40%) were mixed. This mixture was diluted with a MIBK / cyclopentanone mixed solvent (weight ratio 70 / 30) so that the solid content concentration was 30%, to prepare a coating liquid (C2) for forming a hard coat layer.

[0102] A transparent plastic film substrate (TAC, manufactured by Konica Minolta, Inc., product name "KC2UA") was prepared as a light-transmitting substrate. This light-transmitting substrate (transparent plastic film substrate) was the same as the light-transmitting substrate (A) of Example 1. The hard coat layer-forming coating liquid (C2) was applied (coated) to one surface of the transparent plastic film substrate using a bar coater to form a coating layer (coating layer). Then, the transparent plastic film substrate on which this coating layer was formed was transported to a drying process. In the drying process, the coating layer was dried by heating at 80°C for 1 minute to form a coating film. Thereafter, the coating film was irradiated with a high-pressure mercury lamp with an integrated light amount of 240 mJ / cm. 2 The coating film was cured by irradiating it with ultraviolet light of 1000 W to form a hard coat layer having a thickness of 2.0 μm. In this manner, a hard coat film of Comparative Example 2 in which the hard coat layer was formed on the light-transmitting substrate was obtained.

[0103] [Comparative Example 3] An optical film having a resin layer (hard coat layer) formed on a light-transmitting substrate was produced in the following manner.

[0104] As the resin contained in the hard coat layer, 40 parts by weight of ultraviolet-curable acrylate resin (manufactured by Toa Gosei Co., Ltd., product name "M-920", solid content 100%) and 60 parts by weight of ultraviolet-curable acrylate resin (manufactured by Mitsubishi Chemical Corporation, product name "UV-1700TL", solid content 80%) were prepared. Per 100 parts by weight of the resin solid content of the resin, 3 parts by weight of photopolymerization initiator (manufactured by BASF, product name "OMNIRAD907") and 0.50 parts by weight of leveling agent (manufactured by Kyoeisha Chemical Co., Ltd., product name "LE-303", solid content 40%) were mixed. This mixture was diluted with a MIBK / cyclopentanone mixed solvent (weight ratio 70 / 30) so that the solid content concentration was 30%, to prepare a coating liquid (C3) for forming a hard coat layer.

[0105] A transparent plastic film substrate (TAC, manufactured by Konica Minolta, Inc., product name "KC2UA") was prepared as a light-transmitting substrate. This light-transmitting substrate (transparent plastic film substrate) was the same as the light-transmitting substrate (A) of Example 1. The hard coat layer-forming coating liquid (C3) was applied (coated) to one surface of the transparent plastic film substrate using a bar coater to form a coating layer (coating layer). Then, the transparent plastic film substrate on which this coating layer was formed was transported to a drying process. In the drying process, the coating layer was dried by heating at 80°C for 1 minute to form a coating film. Thereafter, the coating film was irradiated with a high-pressure mercury lamp with an integrated light amount of 240 mJ / cm. 2 The coating film was cured by irradiating it with ultraviolet light of 1000 W to form a hard coat layer having a thickness of 2.0 μm. In this manner, a hard coat film of Comparative Example 3 in which the hard coat layer was formed on the light-transmitting substrate was obtained.

[0106] [Measurement of silicon atom ratio] For the optical films (hard coat films) of each of the Examples and Comparative Examples, the ratio of the number of silicon atoms to the total number of carbon, nitrogen, oxygen and silicon atoms was measured in the resin layer (A) or the resin layer of the Comparative Example at a depth of 1 nm from the surface opposite the light-transmitting substrate (A) or the light-transmitting substrate of the Comparative Example by XPS measurement according to the measurement method described below. (XPS measurement) The atomic ratio of silicon (Si) atoms in the range of 1 nm depth from the surface of the hard coat resin layer on the opposite side of the light-transmitting substrate in the hard coat films of the examples and comparative examples was measured by XPS (X-ray photoelectron spectroscopy). XPS, i.e., X-ray photoelectron spectroscopy (XPS: X-ray Photoelectron Spectroscopy), is also called ESCA (Electron Spectroscopy for Chemical Analysis). As for the measurement conditions, the hard coat film as the measurement sample was cut into a 5 mm x 5 mm square, fixed to a sample stage with a Mo (molybdenum) plate, and measured under the conditions shown below. Specifically, first, the measurement sample was wide-scanned and qualitatively analyzed under the following measurement conditions. In addition, narrow scan measurements were performed on C (carbon), N (nitrogen), O (oxygen), Si (silicon), and F (fluorine) at a depth of 1 nm, and the ratio (%) of Si (silicon) atoms was calculated, with the sum of the total atomic numbers of C (carbon), N (nitrogen), O (oxygen), Si (silicon), and F (fluorine) being 100%. XPS measurement conditions: Measurement sample: Hard coat film 5mm x 5mm square Equipment; Quantera SXM manufactured by ULVAC-PHI X-ray source ; Monochrome Al Ka. Xray Setting; 200μmφ[15kV, 30W] Photoelectron take-off angle: 10 degrees to the sample surface (analysis depth: 1 nm) Bond energy correction: The peak due to the CC bond in the C1s spectrum is corrected to 285.0 eV.

[0107] [Check for repelling] The hard coat films (optical films) of each of the above-mentioned Examples and Comparative Examples were cut (cut) into 440 mm x 1000 mm squares to prepare measurement samples. The presence or absence of cissing (display unevenness) was confirmed for these measurement samples by the following measurement methods of orange light reflection test, Z light reflection test, point light source transmission test, and fiber light reflection test. As a result, optical films that did not have cissing by all of the following measurement methods were judged to be "no cissing", and optical films that had cissing by one or more measurement methods were judged to be "present with cissing".

[0108] <How to check for repelling: Orange light reflex test> Orange light (Funatec, model number "FNA-35") was applied parallel to the hard coat coated surface of the hard coat film (the surface on the side of the light-transmitting substrate (A) on which the resin layer (B) was formed, or the surface on the side of the light-transmitting substrate in the comparative example on which the resin layer was formed; the same applies below) from a position 300 mm away. As a result, when the hard coat coated surface was observed at an angle of 45 degrees from the measurement sample and from a position 300 mm away from the center of the hard coat coated surface, samples in which cissing (display unevenness) was visible were rated "with cissing" and samples in which cissing was not visible were rated "without cissing."

[0109] <How to check for repelling: Z light reflection test> A Z light (manufactured by Yamada Electric Co., Ltd., model number "Z-208") was irradiated from a position 400 mm away at an angle of 45 degrees to the hard coat coated surface of the hard coat film, which was a measurement sample. As a result, when the hard coat coated surface was observed from a position 300 mm away from the center of the hard coat coated surface at an angle of 45 degrees (90 degrees from the light source) from the measurement sample, samples in which cissing (display unevenness) was visible were rated as "with cissing," and samples in which cissing was not visible were rated as "without cissing."

[0110] <How to check for repelling: Point light source transmission inspection> A point light source (manufactured by Hamamatsu Photonics, model number "L8425-01") was irradiated at an angle of 45 degrees to the hard-coated surface of the hard-coated film, which was a measurement sample, from a position 560 mm away from the center of the hard-coated surface. The irradiated light was transmitted through the measurement sample, and the transmitted light was projected onto a whiteboard installed at a position 1050 mm away from the point light source. That is, the light irradiation and the projection of the transmitted light were performed in a state in which the measurement sample was sandwiched between the point light source and the whiteboard (positioned between the point light source and the whiteboard). When the transmitted light projected onto the whiteboard under these conditions was visually observed, samples in which repelling (display unevenness) was visible were judged to have "repelling" and samples in which repelling was not visible were judged to have "no repelling."

[0111] <How to check for repelling: Fiber light reflection test> A fiber light (manufactured by MEC Co., Ltd., model number "INS-1303-103" (custom-made)) was irradiated at an angle of 45 degrees to the hard-coated surface of the hard-coated film, which was the measurement sample, from a position 400 mm away from the center of the hard-coated surface. As a result, when the hard-coated surface was observed at an angle of 45 degrees (90 degrees from the light source) from the measurement sample and from a position 300 mm away from the center of the hard-coated surface, samples in which the outline of cissing (display unevenness) was visible only for strong defects were rated as "with cissing," and samples in which the outline was not visible were rated as "without cissing."

[0112] [Production of hard coat film (optical film) having other layer (C)] A surface protective film with adhesive "E-MASK (product name)" manufactured by Nitto Denko Corporation was attached as the other layer (C) and adhesive layer to the hard coat film (optical film) of each of the above-mentioned Examples and Comparative Examples to produce a hard coat film (optical film) having the other layer (C). The surface protective film "E-MASK (product name)" was produced in three types as follows (1), (2), and (3). For the hard coat film (optical film) of each of the above-mentioned Examples and Comparative Examples, three types of hard coat films (optical films) having the other layer (C) were produced corresponding to the following "E-MASK (product name)" (1), (2), and (3). The measurement results of the characteristics of "ring marks", "contamination", and "stop marks" described later were the same for all three types corresponding to the following "E-MASK (product name)" (1), (2), and (3).

[0113] [Method of manufacturing E-MASK (1)] E-MASK (1) was produced as follows.

[0114] (Manufacturing of coating agents) A dispersion containing 25% polyester resin as a binder (product name "Binalol MD-1480", manufactured by Toyobo Co., Ltd. (aqueous dispersion of saturated copolymer polyester resin) (binder dispersion)) was prepared. In addition, an aqueous dispersion of carnauba wax (wax ester) as a slipping agent (slip agent dispersion) was prepared. Furthermore, an aqueous solution containing 0.5% poly(3,4-dioxythiophene) (PEDOT) and 0.8% polystyrene sulfonate (number average molecular weight 150,000) (PSS) as a conductive polymer (product name "Baytron P", manufactured by HC Stark Co., Ltd.) (conductive polymer aqueous solution) was prepared.

[0115] 100 parts of the binder dispersion in terms of solid content, 30 parts of the slip agent dispersion in terms of solid content, 50 parts of the conductive polymer aqueous solution in terms of solid content, and a melamine-based crosslinking agent were added to a mixed solvent of water and ethanol in a mass ratio of 1:1, and the mixture was thoroughly mixed by stirring for about 20 minutes. In this way, a coating agent with a NV of about 0.15% was produced.

[0116] (Formation of topcoat layer) A transparent polyethylene terephthalate (PET) film having a thickness of 38 μm, a width of 30 cm, and a length of 40 cm, one side of which (first side) was corona-treated, was prepared. The above-mentioned coating agent was applied to the corona-treated side of this PET film with a bar coater, and the film was dried by heating at 130° C. for 2 minutes. In this way, a substrate (substrate with topcoat) having a transparent topcoat layer having a thickness of 10 nm on the first side of the PET film was produced.

[0117] (Production of Pressure-Sensitive Adhesive Composition) In a four-neck flask equipped with a stirring blade, a thermometer, a nitrogen gas inlet tube, and a condenser, 200 parts by weight of 2-ethylhexyl acrylate, 8 parts by weight of 2-hydroxyethyl acrylate, 0.4 parts by weight of 2,2'-azobisisobutyronitrile as a polymerization initiator, and 312 parts by weight of ethyl acetate as a solvent were charged, and nitrogen gas was introduced while gently stirring. The liquid temperature in the flask was kept at around 65°C, and a polymerization reaction was carried out for 6 hours to produce an acrylic polymer solution (40% by weight). The weight average molecular weight of the acrylic polymer was 540,000, the glass transition temperature (Tg) was -68°C, and the acid value was 0.0.

[0118] The acrylic polymer solution (40% by weight) was diluted to 20% by weight with ethyl acetate, and 0.3 parts by weight of polyoxyethylene nonylpropenyl phenyl ether ammonium sulfate (trade name "Aqualon HS-10", Daiichi Kogyo Seiyaku Co., Ltd.), which is an anionic surfactant; 3 parts by weight of an isocyanurate of hexamethylene diisocyanate (trade name "Coronate HX", Nippon Polyurethane Industry Co., Ltd.), which is a crosslinking agent; 0.03 parts by weight of dibutyltin dilaurate (trade name "OL-1", Tokyo Fine Chemical Co., Ltd., 0.5% by weight ethyl acetate solution), which is a crosslinking catalyst; and 3 parts by weight of acetylacetone, which is a crosslinking retarder, were added relative to the total solvent amount, and the mixture was mixed and stirred to produce an acrylic pressure-sensitive adhesive composition.

[0119] (Production of E-MASK(1)) A release sheet was prepared in which one side of a PET film was subjected to a release treatment with a silicone-based release treatment agent. The acrylic adhesive composition was applied to the release surface (the surface subjected to the release treatment) of this release sheet, and dried at 130°C for 1 minute to form an acrylic adhesive layer (adhesive layer) having a thickness of 10 μm. The acrylic adhesive layer was attached to the other surface (second surface, i.e., the surface on which the topcoat layer was not provided) of the topcoat-attached substrate, and then aged (aged) for 3 days in an environment of 50°C and 15% RH to obtain E-MASK (1), which is a surface protection film (adhesive sheet). This surface protection film (E-MASK (1)) has the topcoat-attached substrate as the other layer (C), and has the acrylic adhesive layer as the adhesive layer.

[0120] [Method of manufacturing E-MASK (2)] A surface protection film (E-MASK(2)) was produced by the same manufacturing method as that of E-MASK(1) except that the thickness of the acrylic adhesive layer (adhesive layer) was changed from 10 μm to 20 μm. This surface protection film (E-MASK(2)) has the topcoat-attached substrate as the other layer (C) and the acrylic adhesive layer as the adhesive layer.

[0121] [Method of manufacturing E-MASK (3)] E-MASK (3) was produced as follows.

[0122] (Production of (meth)acrylic polymer) In a four-neck flask equipped with a stirring blade, a thermometer, a nitrogen gas inlet tube, and a condenser, 100 parts by weight of 2-ethylhexyl acrylate (2EHA), 10 parts by weight of 4-hydroxybutyl acrylate (4HBA), 0.02 parts by weight of acrylic acid (AA), 0.2 parts by weight of 2,2'-azobisisobutyronitrile as a polymerization initiator, and 157 parts by weight of ethyl acetate were charged, and nitrogen gas was introduced while gently stirring. The liquid temperature in the flask was kept at around 65°C, and a polymerization reaction was carried out for 6 hours to produce a (meth)acrylic polymer solution (40% by weight). The weight average molecular weight of the acrylic polymer was 540,000, and the glass transition temperature (Tg) was -67°C.

[0123] (Production of acrylic oligomers) Into a four-neck flask equipped with a stirring blade, a thermometer, a nitrogen gas inlet tube, a condenser, and a dropping funnel, 100 parts by weight of toluene, 60 parts by weight of dicyclopentanyl methacrylate (DCPMA) (product name: FA-513M, Hitachi Chemical Co., Ltd.), 40 parts by weight of methyl methacrylate (MMA), and 3.5 parts by weight of methyl thioglycolate as a chain transfer agent were added. Then, after stirring for 1 hour under a nitrogen atmosphere at 70°C, 0.2 parts by weight of 2,2'-azobisisobutyronitrile was added as a polymerization initiator, and the mixture was reacted at 70°C for 2 hours, then at 80°C for 4 hours, and then at 90°C for 1 hour to obtain an acrylic oligomer. The weight average molecular weight of the acrylic oligomer was 4000, and the glass transition temperature (Tg) was 144°C.

[0124] (Adhesive solution manufacturing) The (meth)acrylic polymer solution (40% by weight) was diluted to 20% by weight with ethyl acetate, and 500 parts by weight (solid content 100 parts by weight) of this solution was mixed with the acrylic oligomer (solid content 0.5 parts by weight), 2 parts by weight (solid content 0.2 parts by weight) of a solution obtained by diluting an organopolysiloxane having an oxyalkylene chain (KF-353, manufactured by Shin-Etsu Chemical Co., Ltd.) as a silicone component to 10% with ethyl acetate, and lithium bis(trifluoromethanesulfonyl)imide (LiN(CF3SO2)2:LiTFSI, manufactured by Tokyo Chemical Industry Co., Ltd.) to 1% with ethyl acetate as an alkali metal salt (ionic compound) as an antistatic agent. 15 parts by weight of the diluted solution (solid content 0.15 parts by weight), 3.5 parts by weight (solid content 3.5 parts by weight) of an isocyanurate of hexamethylene diisocyanate (manufactured by Nippon Polyurethane Industry Co., Ltd., Coronate HX), which is a trifunctional isocyanate compound, as a crosslinking agent, 0.3 parts by weight (solid content 0.3 parts by weight) of 1,3-bis(isocyanatomethyl)cyclohexane (manufactured by Mitsui Chemicals, Inc., Takenate 600), which is a bifunctional isocyanate compound, and 2 parts by weight (solid content 0.02 parts by weight) of dibutyltin dilaurate (1 wt% solution in ethyl acetate) as a crosslinking catalyst were added, and the mixture was mixed and stirred to produce an acrylic adhesive solution.

[0125] (Manufacture of antistatic film) An antistatic agent solution was prepared by diluting 10 parts by weight of an antistatic agent (Solvex Corporation, Microsolver RMd-142, mainly composed of tin oxide and polyester resin) with a mixed solvent consisting of 30 parts by weight of water and 70 parts by weight of methanol.

[0126] The obtained antistatic agent solution was applied onto a polyethylene terephthalate (PET) film (thickness: 38 μm) using a bar coater, and the solvent was removed by drying at 130° C. for 1 minute to form an antistatic layer (thickness: 0.2 μm), thereby producing an antistatic treated film.

[0127] (Production of E-MASK(3)) The acrylic adhesive solution was applied to the surface opposite to the antistatic treated surface of the antistatic treated film, and heated at 130°C for 2 minutes to form an adhesive layer having a thickness of 15 μm. Next, the silicone-treated surface of a polyethylene terephthalate film (thickness 25 μm) having one side silicone-treated was bonded to the surface of the adhesive layer to obtain E-MASK (3), which is a surface protection film (adhesive sheet). This surface protection film (E-MASK (3)) has the antistatic treated film as the other layer (C), and the acrylic adhesive layer as the adhesive layer.

[0128] [Water contact angle measurement] The water contact angle d2 of the adhesive layer surface was measured for the hard coat film (optical film) having the other layer (C) produced as described above by the following measurement method. That is, first, the hard coat film (optical film) having the other layer (C) was left to stand for 24 hours under the conditions of room temperature (24±2°C) and relative humidity (50±20%), and then the other layer (C) was peeled off to expose the adhesive layer. Next, using a water contact angle measuring device (trade name "DM-301", manufactured by Kyowa Interface Science Co., Ltd.), about 4.0 μL of water droplets were dropped on the adhesive layer surface to which the other layer (C) was attached under an atmosphere of room temperature (24±2°C) and relative humidity (50±20%) by the liquid drop method, and the angle formed by the tangent line of the adherend surface and the end of the dropped water droplet 1 second after the drop was measured, and was taken as the water contact angle (°). Furthermore, the same measurement was performed at five points within the measurement sample, and the average value of the measurements at the five points was taken as the water contact angle d2 (°) of the adhesive layer surface.

[0129] Furthermore, using the same method, the water contact angle d1 (°) of the surface of the resin layer (B) in the optical films (hard coat films) of each of the examples and comparative examples, in which the adhesive layer and the other layer (C) were not present on the surface of the resin layer (B), was measured.

[0130] The measurement results of the water contact angles d1 and d2 are shown in the following Tables 1 to 6. As shown in the following Tables 1 to 6, regardless of whether E-MASK (1), E-MASK (2), or E-MASK (3) was used, the water contact angle d2 on the adhesive layer surface was 90% or less (a decrease of 10% or more) of the water contact angle d1 on the resin layer (B) surface.

[0131] [Table 1]

[0132] [Table 2]

[0133] [Table 3]

[0134] [Table 4]

[0135] [Table 5]

[0136] [Table 6]

[0137] [Product SPV Test] The hard coat film (optical film) having the other layer (C) produced as described above was measured and evaluated for the characteristics of "ring marks", "contamination" and "stop marks" by the following measurement methods. These measurements and evaluations are collectively referred to as "product SPV test" in this embodiment.

[0138] <Ring marks: Evaluation method> The hard coat film (optical film) having the other layer (C) was cut into a 40 mm x 40 mm square to prepare a measurement sample. The light-transmitting substrate side of this measurement sample was attached to an acrylic plate with adhesive, and then the protective film (the other layer (C)) of the measurement sample was once peeled off and the measurement sample was reattached with air bubbles in it. This was left for a predetermined time (120 hours or 240 hours) under conditions of room temperature (24 ± 2 ° C.) and relative humidity (50 ± 20%), and then the protective film was peeled off to check whether traces of air bubbles were visible. <Ring marks: criteria> If the ring marks were not visible even outside of a darkroom after leaving it for 240 hours, it was judged as ◯, and if the ring marks were visible under the same conditions, it was judged as ×.

[0139] Contamination: Evaluation method The hard coat film (optical film) having the other layer (C) was cut into a 40 mm x 40 mm square to prepare a measurement sample. The light-transmitting substrate side of this measurement sample was attached to an acrylic plate with adhesive, and placed in an oven under a predetermined condition (60°C, 60°C / humidity 90%). As the oven, a thermostat (manufactured by Espec Corporation, product name PH(H)-202) or a low-temperature thermohygrostat (manufactured by Espec Corporation, product name PL-2J) was used. After that, the measurement sample was taken out at a predetermined time (120 hours, 240 hours, or 500 hours), and the protective film (the other layer (C)) of the measurement sample was peeled off. An adhesive tape (manufactured by Nichiban Corporation, product name "Large Cellophane Tape CT405AP-24") was attached to the surface of the adhesive layer after the peeling, and then the contamination was confirmed by visual inspection. Contamination: Criteria If no contamination was visible even outside the darkroom after leaving it for 500 hours, it was judged as ◯, and if contamination was visible under the same conditions, it was judged as ×.

[0140] <Stop Mark: Evaluation Method> The hard coat film (optical film) having the other layer (C) was cut into a 25 mm x 100 mm square to prepare a measurement sample. The light-transmitting substrate side of this measurement sample was attached to an acrylic plate with adhesive, and placed in an oven under specified conditions (60°C, 40°C / humidity 92%). As the oven, a thermostat (manufactured by Espec Corporation, product name PH(H)-202) or a low-temperature thermohygrostat (manufactured by Espec Corporation, product name PL-2J) was used. After that, the measurement sample was taken out at a specified time (120 hours), and the peeling was stopped once when half of the area of ​​the protective film (the other layer (C)) of the measurement sample was peeled off, and the remaining protective film was peeled off. It was confirmed by visual inspection whether a stop mark (a trace of the protective film) was visible. <Stop mark: Judgment criteria> If the stop mark was not visible even outside the darkroom after leaving it for 120 hours, it was judged as ◯, and if the stop mark was visible under the same conditions, it was judged as ×.

[0141] The silicon atom number ratio (Si element ratio), the presence or absence of cissing, and the product SPV test results measured as described above are summarized in the following Table 7. In the following Table 7, "Si element ratio at 1 nm of HC surface" means the ratio of the number of silicon atoms to the total number of carbon, nitrogen, oxygen, and silicon atoms at a depth of 1 nm from the surface of the resin layer (A) or the resin layer of the comparative example opposite to the light-transmitting substrate (A) or the light-transmitting substrate of the comparative example.

[0142] [Table 7]

[0143] As shown in Table 7, the optical films of the examples that satisfy all the requirements of the present invention did not have any cissing and all the product SPV test results were good, so it was confirmed that display characteristic defects were suppressed. In contrast, the Si element ratio of Comparative Example 2 was 4.7%, which did not satisfy the condition of the present invention (5.0 to 9.0%). As a result, the product SPV test result of Comparative Example 2 was good, but there was cissing. Furthermore, the Si element ratio of Comparative Example 3 was 9.2%, which did not satisfy the condition of the present invention (5.0 to 9.0%). As a result, the product SPV test result of Comparative Example 3 was poor, although there was no cissing. Furthermore, the Si element ratio of Comparative Example 1 was 1.2%, which was significantly different from the condition of the present invention (5.0 to 9.0%). As a result, there were many cissings in Comparative Example 1. Therefore, it was clear that the optical film of Comparative Example 1 was not suitable for practical use even without checking the product SPV test result, so the product SPV test was not performed. [Industrial Applicability]

[0144] As described above, according to the present invention, it is possible to provide an optical film, an optical film manufacturing method, an optical member, and an image display device in which display characteristic defects are suppressed or prevented. The use of the optical film of the present invention is not particularly limited, and it can be used, for example, in image display devices for any of a variety of uses. [Explanation of symbols]

[0145] 10, 10' Optical film 11 Light-transparent base material (A) 12 Anti-glare layer (B) 12a Resin layer forming resin 12b particles 12c Thixotropic Agents 13 Adhesive layer 20 Other layers (C)

Claims

1. A resin layer (B) is formed on a light-transmitting substrate (A), The element constituting the resin layer (B) contains silicon, An optical film, characterized in that the number of atoms in the resin layer (B) at a depth of 1 nm from the surface opposite to the light-transmitting substrate (A) satisfies the following mathematical formula (1): 5.0≦[(n Si / n total )×100]≦9.0 (1) In the formula (1), n total is the sum of the number of carbon, nitrogen, oxygen and silicon atoms, and n Si is the number of silicon atoms.

2. 2. The optical film according to claim 1, wherein the resin layer (B) has a thickness of 1.0 to 5.0 μm.

3. The resin layer (B) contains a surface conditioner, 3. The optical film according to claim 1, wherein the surface conditioner contains silicon.

4. 4. The optical film according to claim 3, wherein the surface conditioner comprises a silicon compound having a dimethylsiloxane skeleton.

5. 5. The optical film according to claim 1, wherein the resin layer (B) is formed from a copolymer of an oligomer and a monomer having a functional group.

6. The optical film according to claim 1 , wherein the resin layer (B) is a hard coat layer.

7. The optical film according to claim 1 , further comprising: another layer (C) attached to a surface of the resin layer (B) opposite to the light-transmitting substrate (A) via an adhesive layer.

8. The optical film according to claim 7 , wherein the adhesive layer satisfies the condition of the following mathematical formula (2). (d 1 -d 2 ) / d 1 ≧0.10 (2) In the formula (2), d 1 is the water contact angle (°) of the surface of the resin layer (B) when the adhesive layer and the other layer (C) are not present on the surface of the resin layer (B), and d 2 is the water contact angle (°) of the surface of the adhesive layer after the other layer (C) is peeled off from the adhesive layer.

9. 9. The optical film according to claim 7, wherein the other layer (C) is a glass or resin film.

10. The method includes a resin layer (B) forming step of forming the resin layer (B) on the light-transmitting substrate (A) so as to satisfy the mathematical formula (1), the resin layer (B) forming step includes a coating step of coating a resin layer forming coating liquid on the light-transmitting substrate (A), and a coating film forming step of drying the applied resin layer forming coating liquid to form a coating film, 10. The method for producing an optical film according to claim 1, wherein the resin layer-forming coating liquid contains a resin, a silicon-containing additive, and a dilution solvent.

11. The method for producing an optical film according to claim 10 , wherein the resin layer (B) forming step further comprises a curing step of curing the coating film.

12. The optical film is the optical film according to claim 3 or 4, The method for producing an optical film according to claim 10 or 11, wherein the silicon-containing additive is the surface conditioner.

13. The method for producing an optical film according to claim 10 , wherein the dilution solvent comprises MIBK (methyl isobutyl ketone) and cyclopentanone.

14. An optical member comprising the optical film according to claim 1 .

15. The optical member according to claim 14, which is a polarizing plate.

16. An image display device comprising the optical film according to claim 1 , or the optical member according to claim 14 .

Citation Information

Patent Citations

  • Method for producing antireflection hard coat film, antireflection hard coat film, polarizing plate and image forming apparatus

    JP2010181727A

  • Coating composition, and coating film

    JP2014162889A

  • Resin film, laminate film, optical member, display member, front plate, and production method of laminate film

    JP2016093992A

  • Window film, and method for producing window film

    JP2016165824A

  • JP221746A